A novel smart toolholder with embedded force sensors for milling operations. (1st August 2022) - Zhang, Pengfei; Gao, Dong; Lu, Yong; Wang, Fenglei; Liao, Zhirong
Highlights: A novel smart toolholder based on self-compensating semiconductor strain gauges has been proposed. An integral smart toolholder with unique on-toolholder force sensing units has been developed and tested. The proposed smart toolholder possesses higher flexibility and reconfigurability. The system can measure four-component milling force accurately. The smart toolholder can reliably identify the tool wear condition well. Abstract: In the era of intelligent manufacturing and big data, cutting force has become one of the most important data sources for the machining process, which is not only of significance for offline analysis, but also crucial for online monitoring and control. However, the current table and rotating dynamometers for cutting force sensing meet the problems of cumbersome installation and low integration, which make them still limited to laboratory applications. In this paper, a novel integral smart toolholder with unique on-toolholder force sensing units has been proposed, whereby a measuring part (i.e. the thin-walled beam) has been designed as a separated agent from the supporting part (i.e. the thick beam) by four double T-slots. Moreover, to achieve the high sensitivity, self-compensating semiconductor strain gages were embedded into a standard toolholder with a data acquisition unit as an integrated solution. A mechanistic model has also been developed to decouple the four-component milling force thus to optimise the sensing structure to allow the high-sensitivity while not to reduce the stiffness significantly. To improve integration while allow machining continuously without interruption, a slip ring was utilized to supply power and data transfer with low latency. Owing to the split structure design, the proposed smart toolholder possessed improved flexibility and reconfigurability, and it could be used in the assembly of multi-type machining spindles and multi-size tools. Various tests were also performed to determine the static and dynamic characteristics of the proposed smart toolholder. The results showed that the proposed smart toolholder has high sensitivity, linearity, repeatability, and hysteresis. A further cutting experiment demonstrated that the proposed smart toolholder can measure the four-components milling force accurately and its relative deviation is less than 10% with the comparison of off-the-shelf dynamometer, which provides a smart solution for monitoring the cutting tool condition.